Enhancing Supply Chain Resilience By Addressing The Achilles Heel Of Information Sharing - Tan, Hwee Chin (2019)
The risks of information leakage associated with information sharing across supply chains are still not well-defined. It is clear that managerial approaches in mitigating such risks are needed. Therefore, this study demonstrates pathways to supply chain resilience derived from linkages of information leakage to information sharing effectiveness with mitigation approaches. It shows the information sharing effectiveness enables quick response to leakage by mitigation approaches and increase resilience, which might provide a competitive edge over their competitor across a supply chain. This study designed a sequential exploratory mixed method approach by combining qualitative and quantitative studies. First, purposeful sampling in a qualitative study was adopted involving semi-structured interviews with five cases of Malaysia Multinational Corporations predominantly in the manufacturing sector. Interviews with managers gain deeper insights into the risks of information leakage involved and developed appropriate mitigation strategies when sharing information with supply chain partners. The main study findings are synthesized into a theoretical framework that revealed organization ethical climate and information security culture are new useful approaches to mitigate the devastating consequences on information sharing effectiveness. Second, purposive sampling in a quantitative study was conducted to empirically verify the framework by using a questionnaire distributed to Malaysian MNCs, predominately in the manufacturing sector.